THE INFLUENCE OF WIND, TEMPERATUR AND RAINFALL ON THE CATCH OF FISHERMEN IN FISHING PORTOF BATAM CITY - Sihotang, Nico Darminto; Galib, Musrifin; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe fish catches of fishermen was strongly influenced by wind, temperature and rainfall. This research was conducted in December 2018 – February 2019 in the Barelang Fishing Port Batam City. The purpose of this research are to know the patterns of changes in wind, temperature and rainfall that occur in Batam City and the influenced on fishermen fish catches in Batam City and to determine the good time/season for fishing operations. The research used survey method, primary data obtained using questionnaires and secondary data obtained from Barelang Fishing Port, BMKG Hang Nadim amd Batam City Fisheries Service. The hypothesis was tested using a simple regression test. Wind, temperature and rainfall data were analyzed using Microsoft Excel 2010. The results showed that the relationship between wind speed with fishermen fish catches is opposite each other, temperature with fishermen fish catches is directly proportional and intensity of rainfall with fishermen fish catches is opposite each other. The good season to catch fishing is in the transisition season 2 (October to November) and transition 1 (March to May). Analysis of climate change trends in Batam City shows that the average of wind speed tends to decrease every year, the average of temperature tends to increase every year and intensity of rainfall tends to decrease every year. Keywords :Catch, Wind Speed, Temperature, Intensity of Rainfall, Climate Change